Nawoływanie do popełnienia przestępstwa a wolność słowa na podstawie Brandenburg v. Ohio - Zowczak, Maciej; Żyła, Mateusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The purpose of this study was to lead some reflection upon the freedom of speech in Polish legal order by example of the certain category of speech- advocacy of unlawful conduct. For this purpose the authors focused on comparison of Polish and American law and respective jurisdiction approach. The comparison was mainly based on landmark United States Supreme Court ruling Brandenburg v. Ohio from 1969r. Furthermore, the study examined the way to accomplish this approach by investigating previous precedent-setting cases. The summary consists results of the studies and embodies authors stance on this legal issue. The authors postulate the adoption into the Polish legal framework another protected category of speech which is advocacy of unlawful conduct.
Keywords: Brandenburg Test; judge Holmes; Brandenburg v Ohio; advocacy; freedom of expression; Constitution; Clarence Brandenburg; clear and present danger test; First Amendment; 255 Polish Penal Code; freedom of speech; advocacy of unlawfull conduct